2011
DOI: 10.1128/jcm.02153-10
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity among Korean Candida albicans Bloodstream Isolates: Assessment by Multilocus Sequence Typing and Restriction Endonuclease Analysis of Genomic DNA by Use of BssHII

Abstract: Multilocus sequence typing (MLST) has been successfully applied to the epidemiology of Candida albicansisolates not only within the hospital setting but also in multiple locations nationwide. We performed MLST to investigate the genetic relatedness among bloodstream infection (BSI) isolates of C. albicans recovered from 10 Korean hospitals over a 12-month period. The 156 isolates yielded 112 unique diploid sequence types (DSTs). While 95 DSTs were each derived from a single isolate, 17 DSTs were shared by 61 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 21 publications
3
57
2
Order By: Relevance
“…Phylogenetic analysis of our 104 isolates, together with 1485 known DSTs, revealed that 94.2 % of them clustered within 14 of 18 known clades, (clades 1, 3, 4, 6, 7, 8, 9, 11, 12, 14, 15, 16, 17 and 18) and 5.8 % did not cluster within known clades (Fig. 1) (Gong et al, 2012;Odds et al, 2007;Shin et al, 2011). Shin et al (2011) first reported clade 18 as a novel group predominantly consisting of Asian isolates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Phylogenetic analysis of our 104 isolates, together with 1485 known DSTs, revealed that 94.2 % of them clustered within 14 of 18 known clades, (clades 1, 3, 4, 6, 7, 8, 9, 11, 12, 14, 15, 16, 17 and 18) and 5.8 % did not cluster within known clades (Fig. 1) (Gong et al, 2012;Odds et al, 2007;Shin et al, 2011). Shin et al (2011) first reported clade 18 as a novel group predominantly consisting of Asian isolates.…”
Section: Discussionmentioning
confidence: 99%
“…1) (Gong et al, 2012;Odds et al, 2007;Shin et al, 2011). Shin et al (2011) first reported clade 18 as a novel group predominantly consisting of Asian isolates. Indeed, Gong (2012) found that 66.7 % of the strains collected in north China were within clade 18.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MLST is a powerful and useful technique for understanding the epidemiological and evolutionary relationships of pathogenic micro-organisms (Taylor & Fisher, 2003;Urwin & Maiden, 2003;Maiden, 2006;Cliff et al, 2008;Odds & Jacobsen, 2008;Da Matta et al, 2010;Shin et al, 2011). Prevalence of C. albicans infections in the BICU of the Zare hospital (Sari, Iran) led us to investigate the epidemiological relationship of 30 isolates involved using the MLST method.…”
Section: Discussionmentioning
confidence: 99%